(untitled) (Research, Society and Development, 2019)
The objective of this study is to provide information on personal finance in the university public. The methodology used is qualitative, consisting of a non-university field study. As a result, the evidence that the existence of less knowledge about the subject, the importance of updating, and the use of an aid tool to understand their expenses, is a perspective of university students. Finally, the study concluded that students still do not have a way to save money, but intend in the future on the possibility of a reserve for eventual expenditure.